CLUSTER COMPUTING OF HIGH FREQUENCY ELECTROMAGNETIC FIELD PROPAGATION - Walendziuk, Wojciech; Forenc, Jaroslaw; Jordan, Andrzej (International Journal of Computing, 2014)
The paper presents parallel implementations of the FDTD (Finite Differences Time Domain) method in cluster systems of PC’s. Those two- and three- dimensional algorithms are based on the stripes decomposition of the analyzed area. What is more, the communication among particular computation nodes building the cluster system is discussed. On the basis of the obtained results, the analysis of the efficiency of the presented algorithms was done.